In Vitro Activities of Colistin and Sitafloxacin Combinations against Multidrug-, Carbapenem-, and Colistin-Resistant Acinetobacter baumannii Using the Broth Microdilution Checkerboard and Time-Kill Methods - Vipavee Rodjun; Jantana Houngsaitong; Preecha Montakantikul; Taniya Paiboonvong; Piyatip Khuntayaporn; Pattareeya Yanyongchaikit; Pusana Sriyant (MDPI AG, 2020)
Drug-resistant Acinetobacter baumannii (A. baumannii) infections are a critical global problem, with limited treatment choices. This study aims to determine the in vitro activities of colistin-sitafloxacin combinations against multidrug-, carbapenem- and colistin-resistant A. baumannii (MDR-AB, CRAB, CoR-AB, respectively) clinical isolates from tertiary care hospitals. We used the broth microdilution checkerboard and time-kill methods in this study. Synergy was found using both methods. The colistin-sitafloxacin combination showed synergy in MDR-AB, CRAB, and CoR-AB isolates (3.4%, 3.1%, and 20.9%, respectively). No antagonism was found in any type of drug-resistant isolate. The majority of CoR-AB isolates became susceptible to colistin (95.4%). The time-kill method also showed that this combination could suppress regrowth back to the initial inocula of all representative isolates. Our results demonstrated that the colistin-sitafloxacin combination might be an interesting option for the treatment of drug-resistant A. baumannii. However, further in vivo and clinical studies are required.